Digital Transformation as a Catalyst for High-Quality Development: Examining Total Factor Productivity and ESG Performance in China’s Manufacturing Sector - Cheng , Qin (Journal of Ecohumanism, 2025)
This study investigates the impact of digital transformation on total factor productivity (TFP) and environmental, social, and governance (ESG) performance in Chinese manufacturing firms, exploring the balance between economic output and sustainability for high-quality development. Results reveal two key mechanisms: innovation and efficiency. Digital transformation boosts productivity through open innovation and data-driven resource allocation while enhancing ESG performance via green technologies and efficient supply chains. The external institutional environment, including business climate and marketization, significantly influences its effectiveness. Over time, digital transformation’s impact on TFP diminishes, but its role in promoting ESG performance strengthens as firms advance in sustainability. This research offers insights for enterprises and policymakers on leveraging digitalization to achieve sustainable growth, emphasizing the need to clarify specific pathways within China’s manufacturing sector.